If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-4=3(x-1)+10
We move all terms to the left:
3x-4-(3(x-1)+10)=0
We calculate terms in parentheses: -(3(x-1)+10), so:We get rid of parentheses
3(x-1)+10
We multiply parentheses
3x-3+10
We add all the numbers together, and all the variables
3x+7
Back to the equation:
-(3x+7)
3x-3x-7-4=0
We add all the numbers together, and all the variables
-11!=0
There is no solution for this equation
| 5-x=3x+45 | | 1.2x-1.97=-2.69 | | -2x+4x=7 | | 5x-2=5(x-1)+9 | | -8m+8=-40 | | 4(3q+10)=-6(2q-9) | | 4(3x-8)-11=2 | | 6y-10=45 | | 17b=18 | | 10p+5=55 | | F(3)=22x+11 | | c-13=14 | | 23=-3x+80 | | 8k=104 | | F(x)=22x+11 | | |2x-8|+5=11 | | n/2+2=-4 | | 12=w/5-8 | | 2.3=-0.6x+5 | | 2x+23=5x−4 | | −21+a=7(6a−3) | | 7x-9-4x+22=90 | | x+3+9x+5=47 | | 12-(2-x)=4(x-3)-7x | | p/13=2 | | 14/x=8/72 | | 3+9x=0 | | 79=94-d | | -8n-2=-2 | | 16=2(y-7y) | | 4)x+2)=28 | | 6x+7=6x+16 |